From glucose to histone modification: sex-specific metabolic responses to ketogenic therapy in VM/Dk mice - Moss, Sara E.; Poff, Angela M.; Moss, Apryl; DeBlasi, Janine M.; D’Agostino, Dominic P. (Frontiers in Nutrition, 2025)
IntroductionThe assessment of sex-specific effects in pre-clinical models is critical for improving the translatability of findings to clinical applications. However, preclinical studies often combine sexes or focus exclusively on one sex, including research utilizing syngeneic cancer models. Considering sex differences is particularly important in metabolic studies, as males and females exhibit distinct body compositions, hormone profiles, and metabolic demands.MethodsThis study evaluates sex-specific metabolic responses to ketogenic therapies in VM/Dk mice, including assessments of glucose metabolism, ketone metabolism, and histone modifications linked to metabolism.ResultsOur findings reveal significant sex differences in body weight, circulating metabolites, blood insulin levels, and histone modification profiles.DiscussionWe demonstrate that male and female VM/Dk mice respond differently to ketogenic therapies, with responses varying based on the specific type of therapy applied.